Clomazone impact on fungal network complexity and stability - He, Hairong; Huang, Jiarui; Zhao, Zhenzhu; Feng, Weisheng; Zheng, Xiaoke; Du, Pengqiang (Frontiers in Microbiology, 2023)
Introduction Soil fungal network composition and stability are important for soil functions, but there is less understanding of the impact of clomazone on network complexity and stability. Methods In this work, two agricultural soils were used to investigate the impact of clomazone on fungal network complexity, composition, and stability. The two soils were treated with clomazone solution (0, 0.8, 8, and 80 mg kg−1) and kept in an incubator. Results and Discussion Under the influence of clomazone, the fungal network nodes were decreased by 12–42; however, the average degree was increased by 0.169–1.468 and fungal network density was increased by 0.003–0.054. The keystone nodes were significantly changed after clomazone treatment. Network composition was also impacted. Specifically, compared with control and clomazone treatments in both soils, the shared edges were fewer than 54 in all comparisons, and network dissimilarity was 0.97–0.98. These results suggested that fungal network composition was significantly impacted. The network robustness was increased by 0.0018–0.0209, and vulnerability was decreased by 0.00018–0.00059 in both soils, which indicated that fungal network stability was increased by clomazone. In addition, the functions of network communities were also changed in both soils. These results indicated that clomazone could significantly impact soil fungal networks.